Advances in biocomposite fabrication: Emerging technologies and their potential applications - Siraj, Md. Tanvir; Alshybani, Ibrahem; Payel, Spandan Basak; Shahadat, Muhammad Rubayat Bin; Rahman, Md Zillur (Reference Module in Materials Science and Materials Engineering, 2015)
Biocomposites have emerged as promising materials with a wide range of potential applications in various fields. With the growing demand for sustainable and eco-friendly materials, the fabrication of biocomposites has garnered significant attention from researchers worldwide. This study presents an overview of recent advances in biocomposite fabrication techniques, including electrospinning, filament winding, injection molding, extrusion, nanotechnology, 3D/4D/5D printing, and microfluidic, highlighting the technical procedures, fabricated biocomposites, and limitations that need to be addressed in future research. Electrospinning has shown promising results in producing nanofiber-based biocomposites with improved mechanical and biological properties. Filament winding is used to fabricate high-strength biocomposites for aerospace and automotive applications, whereas injection molding can be employed to produce biocomposites with high-volume fractions of fibers. Extrusion methods are widely employed for blending and processing biocomposites, allowing for the efficient production of various shapes and sizes. Nanotechnology has enabled the production of biocomposites with tailored properties by incorporating nanofillers. 3D/4D/5D printing has revolutionized the fabrication process by allowing the production of complex geometries with high accuracy and reproducibility. Microfluidic techniques can be used to fabricate biocomposite microstructures with controlled porosity. Despite these advancements, challenges remain, such as the limited scalability of some techniques, high production costs, and the need to further optimize mechanical and biological properties. Integrating artificial intelligence in the biocomposite fabrication process can enable the development of more efficient and sustainable manufacturing processes. This study can be useful to researchers and academics in materials science, engineering, biotechnology, industry professionals, policymakers, and regulatory bodies involved in promoting sustainable and eco-friendly materials.